Effect of artificial aging time on torsional fatigue life and cyclic behavior of AA6351 aluminum alloy and evaluation of estimation methods - Betemps M.I.* (2023)
© 2023 John Wiley & Sons Ltd.The effects of artificial-aging time on monotonic properties and torsional fatigue of AA6351 aluminum alloy were studied in this paper. Fatigue tests were carried out by the strain-controlled condition. Monotonic and cyclic torsional behavior, fatigue life, and estimation methods were verified. Results showed the distance between monotonic and cyclic curves progressively decreased as aging time increased from 1 to 2 and 6 h at 170°C. The yield strength values were subsequently 74.5, 110.7, and 142.5 MPa for monotonic torsion and 127, 145, and 160 MPa for cyclic torsion test (half-life). Alloy in all aging times showed similar fatigue life in high cycle (N f > 105 cycles), and time 1 h, longer fatigue life in low cycle (Nf < 104 cycles). All specimens presented cyclic hardening at strain amplitudes ranges tested. The estimation methods showed good prediction for the fatigue parameters.